Synthesis and Solvatochromism of Oxazolone Derivative: Combining Organic Synthesis and Physical Organic Chemistry in a Single Experiment - Taianne D’Angelo Korb; Lucia Helena Franco Martires da Costa; Mauricio Ferreira da Rosa (Orbital: The Electronic Journal of Chemistry, 2022)
This work presents a proposal of experimental activity involving organic synthesis and solvatochromism of an organic molecule, correlating the content of organic chemistry and physical organic chemistry. This experiment presents a good opportunity to work with the classroom some of the content related to the mechanisms of organic reactions and the relationship between energy, electronic states, solute-solvent interactions, spectroscopy, among others in the area of physical chemistry, thus integrating knowledge. Experimentally, we synthesized through the Plöchl-Erlenmeyer method the oxazolonic derivative 4-[(p-N,N-dimethylamino)benzylidene]-2-phenyloxazole-5-one (AZA2) with good yield (78%), while the solvatochromic study showed that this derivative presented reverse solvatochromism; since in non-hydroxyl solvents it presented positive solvatochromism, but in protic solvents it presented negative solvatochromism. These different behaviors can be justified by the different solute-solvent interactions existing in each medium, which favors the prevalence of different mesomeric structures.